2020
DOI: 10.1016/j.nicl.2020.102364
|View full text |Cite
|
Sign up to set email alerts
|

Anterior insular network disconnection and cognitive impairment in Parkinson’s disease

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…We also observed lower ALFF values in the left insula in the PD-Post-DBS group. The insular lobe was thought to regulate DMN, as well as the fronto-parietal network ( Fathy et al, 2020 ), and is associated with cognitive impairment in PD ( Deen et al, 2011 ; Fathy et al, 2020 ). After STN-DBS, the cognitive decline on frontal executive function ( Mikos et al, 2011 ; Lefaucheur et al, 2012 ), particularly verbal fluency ( Okun et al, 2009 ; Mikos et al, 2011 ; Lefaucheur et al, 2012 ), found in many studies is considered to be due to the surgical microlesion ( Mikos et al, 2011 ; Lefaucheur et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed lower ALFF values in the left insula in the PD-Post-DBS group. The insular lobe was thought to regulate DMN, as well as the fronto-parietal network ( Fathy et al, 2020 ), and is associated with cognitive impairment in PD ( Deen et al, 2011 ; Fathy et al, 2020 ). After STN-DBS, the cognitive decline on frontal executive function ( Mikos et al, 2011 ; Lefaucheur et al, 2012 ), particularly verbal fluency ( Okun et al, 2009 ; Mikos et al, 2011 ; Lefaucheur et al, 2012 ), found in many studies is considered to be due to the surgical microlesion ( Mikos et al, 2011 ; Lefaucheur et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…CAMCOG_Total: Cambridge Cognitive Battery Total score, H&Y: Hoehn and Yahr stage, ISCED: International Standard Classification of Education, LEDD: Levodopa equivalent daily dose, PD: Parkinson’s disease, SD: Standard Deviation, UPDRS III: Unified Parkinson’s Disease Rating Scale part III, LEDD: L-DOPA equivalent daily dose.. ^mean and range is reported for these variables.. * p < 0.05, ** p < 0.01. Table adapted from Fathy et al, 2020 28 .…”
Section: Resultsmentioning
confidence: 99%
“…The anterior insula has strong connections with the ACC 13 , and is associated with cognitive control in PD 28 . Since only the dAI, not the vAI, showed network topological alterations of eigenvector and betweenness centrality in PD, we assessed microstructural alteration in the connections between the dAI and ACC only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations